(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
An experiment was conducted in field condition to study the effect of nitrogen-phosphorus fertilization on growth, yield and nutrient content of cabbage. The experiment was laid out in randomize block design with three replications. The yield and yield components were maximized by N3P2 fertilizer treatment. Nutrient content of cabbage varied with fertilizer treatment. The maximum amount of reducing sugar, ascorbic acid, phosphorus were found at the highest rate of N - P fertilization whereas accumulation of titrable acidity, iron, calcium were maximum at the rate of N2P2 treatment. However pH, ash content were more or less same throughout the experiment. Bangladesh J. Sci. Ind. Res. 41(1-2), 41-46, 2006